A cold-resistant and torsion-resistant wind energy control cable and a preparation method thereof
By using a specific proportion of materials and modified white carbon black in the outer sheath layer of the wind energy control cable, the problem of the cable being prone to break in low temperature environments is solved, achieving better cold resistance and mechanical properties.
Patent Information
- Application Number
- CN202210897491.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-07-28
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2042-07-28
AI Technical Summary
In low temperature environments, the cables in the wind farm are prone to become brittle and breakage, resulting in equipment failure and production interruption.
A cold-resistant and torsion-resistant wind energy control cable is designed. The outer sheath layer of the outer sheath is made of a specific proportion of ethylene propylene ternary rubber, chlorinated polyethylene, zinc oxide, fillers, antioxidants, plasticizers, anti-aging agents, vulcanizers and flame retardants. Through the preparation method of modified white carbon black, the compatibility between fillers and matrix materials is improved.
The cable is not prone to cracking in low temperature environments, has better mechanical properties and cold resistance, and can better adapt to extreme environments.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of wind power cables, and in particular to a cold-resistant and torsion-resistant wind power control cable and a preparation method thereof. Background Art
[0002] With the development of global industrialization, the demand for energy is increasing. With the consumption of non-renewable resources such as oil and coal, the demand for the development of clean energy such as solar energy and wind energy is also increasing. As a relatively mature technology, wind power generation has the characteristics of high concentration, short construction period and moderate investment intensity. my country has a vast territory and excellent conditions for wind power generation, so the wind power generation market is also showing a rapid growth trend. With the continuous expansion of the area where wind power generation is used, the construction of wind farms is increasingly moving towards cold areas such as Mobei and Gobi. There are more extreme weather and large temperature differences between day and night. At low temperatures, the cable will become brittle and break, so a cable with good cold resistance is needed. Summary of the invention
[0003] In view of this, the purpose of the present invention is to provide a cold-resistant and torsion-resistant wind energy control cable and a preparation method thereof. The outer sheath material is designed to improve the compatibility between the filler and the matrix material, so that the prepared cable has good cold resistance.
[0004] The present invention solves the above technical problems by the following technical means:
[0005] A cold-resistant and torsion-resistant wind energy control cable, which comprises, from the inside to the outside, a conductor, an isolation layer, an insulating layer, and an outer sheath layer extruded outside the insulating layer; the outer sheath layer comprises the following raw materials in parts by weight: 100-120 parts of ethylene propylene rubber, 20-40 parts of chlorinated polyethylene, 3-5 parts of zinc oxide, 60-80 parts of filler, 1-3 parts of antioxidant, 5-10 parts of plasticizer, 3-4 parts of antioxidant, 10-15 parts of vulcanizer, and 10-15 parts of flame retardant.
[0006] Furthermore, the outer sheath layer comprises the following raw materials in parts by weight: 100 parts of EPDM rubber, 30 parts of chlorinated polyethylene, 4 parts of zinc oxide, 70 parts of filler, 2 parts of antioxidant, 8 parts of plasticizer, 3 parts of antioxidant, 12 parts of vulcanizer, and 12 parts of flame retardant.
[0007] Furthermore, the filler comprises the following raw materials in parts by weight: 15-20 parts of short carbon fibers, 5-10 parts of kaolin, and 20-40 parts of modified white carbon black.
[0008] Furthermore, the filler includes the following raw materials in parts by weight: 18 parts of short carbon fibers, 8 parts of kaolin, and 35 parts of modified white carbon black.
[0009] Furthermore, the preparation method of the modified silica is as follows: the preparation method of the modified silica is as follows: take the pretreated silica, add it to the liquid butadiene rubber, stir and mix, add diisopropylbenzene peroxide, heat to 180-200°C, keep warm and react for 2-3h to obtain the modified silica.
[0010] Further, the pretreatment of the white carbon black is as follows: adding the white carbon black to a mixed acid solution, ultrasonically dispersing the solution, heating the solution to 70-80°C, and refluxing the solution for 20-24 hours. After the reaction is completed, filtering the solution, washing the filter cake with deionized water until the filtrate is neutral, drying the solution, adding the solution to anhydrous ethylenediamine and N,N-dicyclohexylcarboximide, heating the solution to 120-125°C, and refluxing the solution for 48-72 hours. After the reaction is completed, filtering the solution, washing the filter cake with deionized water until the filter cake is neutral, drying the solution, ultrasonically dispersing the solution in xylene, adding maleic anhydride, heating the solution to 80-85°C, and refluxing the solution for 24-48 hours. After the reaction is completed, diluting the solution with 50°C anhydrous ethanol, filtering the solution, washing the filter cake three times with anhydrous ethanol and deionized water, and drying the filter cake for later use.
[0011] The white carbon black of the present application is firstly subjected to an acidification treatment by a mixed acid solution to activate the surface of the white carbon black and introduce more oxygen-containing groups, and then subjected to an amination treatment by anhydrous ethylenediamine and N,N-dicyclohexylcarbocyanine, and then reacted with maleic anhydride to graft the maleic anhydride onto the surface of the white carbon black, which is beneficial to reduce the surface energy of the white carbon black and improve its dispersibility. Meanwhile, through the grafting of maleic anhydride, maleic anhydride and liquid butadiene rubber are reacted in a subsequent modification process, and the butadiene rubber is coated on the surface of the white carbon black under the action of an initiator, diisopropylbenzene peroxide.
[0012] In addition, after the traditional filler is added to the matrix material, a clear boundary will be formed between the filler and the matrix material, which will affect the movement of the molecular chain of the matrix material, thereby causing the toughness of the matrix material to decrease and the glass transition temperature to increase. The filler of the present application, with the addition of modified silica, has a structure with cis-1,4-dimethylbutyl rubber as the shell layer and silica as the core. During use, the external cis-1,4-dimethylbutyl rubber and the matrix material are integrated, blurring the boundary between the filler and the matrix material, increasing the bridging density between the molecules of the matrix material, thereby reducing the glass transition temperature of the matrix material, improving the cold resistance and toughness, and compounding with cis-1,4-dimethylbutyl rubber can also make the core White carbon black can be dispersed more evenly, and because white carbon black and butadiene rubber are connected by maleic anhydride, the position of white carbon black can be limited to a certain extent to prevent it from precipitating during use; secondly, the filler of the present invention also utilizes the synergistic effect of short carbon fibers, kaolin and modified white carbon black. During use, kaolin can improve the cohesion of the matrix material to a certain extent, while the short carbon fibers and modified white carbon black can form a rubber network in the matrix material, increasing the heat transfer of the matrix material, thereby making the outer sheath material vulcanize faster during the preparation process, and the obtained outer sheath layer has better mechanical properties.
[0013] Furthermore, the mixed acid solution is a mixed solution of concentrated sulfuric acid and concentrated nitric acid, and the volume ratio of sulfuric acid to nitric acid is 3:1.
[0014] In addition, the present application also discloses a method for preparing the above-mentioned cold-resistant and torsion-resistant wind energy control cable, the preparation method comprising the following steps:
[0015] S1: The copper rod is drawn, heat treated, tinned, annealed, and twisted to obtain a conductor;
[0016] S2: Wrap the conductor with polyester tape to form an isolation layer;
[0017] S3: Extruding an insulating layer outside the isolation layer;
[0018] S4: Refining the raw materials of the outer sheath to obtain an outer sheath material, and extruding the outer sheath material outside the insulating layer to form an outer sheath layer.
[0019] Further, the preparation method of the outer sheath material is:
[0020] S41: adding EPDM rubber and chlorinated polyethylene into an internal mixer, and mixing until the rubber wraps around the rotor;
[0021] S42: Add zinc oxide, antioxidant, plasticizer, antioxidant and flame retardant, mix for 2-3 minutes, heat to 110-120°C, add short carbon fiber and kaolin in the filler, continue to mix for 2-4 minutes, add modified white carbon black, mix for 5-6 minutes, and remove glue;
[0022] S43: After 3 times of refining on the bag turning machine, the rubber is opened and filtered;
[0023] S44: Add the rubber material into an internal mixer, add a vulcanizing agent, and internally mix at 100-110°C for 2-3 minutes to produce the rubber, and then refining it on a bag turning machine, rolling it on an open mixing mill, and producing sheets to obtain the outer sheath material.
[0024] In summary, this application has the following beneficial effects:
[0025] The cold-resistant and torsion-resistant wind energy control cable of the present invention redesigns the raw materials of the outer sheath material, and the added filler can blur the boundary between the filler and the base material, increase the bridging density between the molecules of the base material, thereby reducing the glass transition temperature of the base material and improving the cold resistance and toughness; at the same time, short carbon fibers and modified white carbon black can form a rubber network in the base material, increase the heat conductivity of the base material, thereby making the outer sheath material vulcanize faster during the preparation process, and the prepared outer sheath layer has better mechanical properties. DETAILED DESCRIPTION
[0026] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0027] Embodiment 1
[0028] Preparation of modified silica
[0029] Pretreatment: Concentrated sulfuric acid and concentrated nitric acid were measured in a volume ratio of 3:1 to prepare a mixed acid solution, white carbon black was added to the mixed acid solution at a solid-liquid ratio of 5g / L, and after ultrasonic dispersion, the temperature was raised to 70°C, and the mixture was refluxed for 24 hours. After the reaction was completed, the mixture was filtered, and the filter cake was washed with deionized water until the filtrate was neutral. After drying, anhydrous ethylenediamine and N, N-dicyclohexylcarboximide with a volume ratio of 1:1 and 10 times the mass of white carbon black were added. The temperature was raised to 125°C, and the mixture was refluxed for 48 hours. After the reaction was completed, the mixture was filtered. The filter cake was washed with deionized water until neutral, dried and ultrasonically dispersed in xylene with a mass of 10 times the mass of white carbon black, maleic anhydride with a mass of 0.5 times the mass of white carbon black was added, the temperature was raised to 80°C, and the reaction was refluxed for 30 hours. After the reaction was completed, 1 / 2 times the volume of a mixed solution of anhydrous ethylenediamine and N,N-dicyclohexylcarboximide was added, diluted with 50°C anhydrous ethanol, filtered, and the filter cake was washed three times with anhydrous ethanol and deionized water respectively, and then dried for use.
[0030] Take the pretreated silica, add it to the liquid butadiene rubber, stir and mix, then add diisopropylbenzene peroxide, raise the temperature to 190°C, and keep the temperature for 3 hours to obtain modified silica, wherein the mass ratio of silica, liquid butadiene rubber and diisopropylbenzene peroxide is 2:1:0.1.
[0031] The prepared modified silica is used as a raw material for a cold-resistant and torsion-resistant wind energy control cable, wherein the filler of this embodiment comprises the following raw materials by weight: 18 parts of short carbon fiber, 8 parts of kaolin, and 35 parts of modified silica. The specific preparation method is as follows:
[0032] S1: The copper rod is drawn, heat treated, tinned, annealed, and twisted to obtain a conductor;
[0033] S2: Wrap the conductor with polyester tape to form an isolation layer;
[0034] S3: Extruding an insulating layer outside the isolation layer;
[0035] S4: Refining the raw materials of the outer sheath to obtain the outer sheath material, specifically:
[0036] S41: 100 parts of EPDM rubber and 30 parts of chlorinated polyethylene are added to an internal mixer and mixed until the rubber wraps around the rotor;
[0037] S42: Add 4 parts of zinc oxide, 2 parts of antioxidant, 8 parts of plasticizer, 3 parts of antioxidant and 12 parts of flame retardant, mix for 3 minutes, heat to 110-120°C, add 70 parts of filler, specifically add short carbon fiber and kaolin first, continue mixing for 4 minutes, add modified white carbon black, mix for 5-6 minutes, and remove glue;
[0038] S43: After 3 times of refining on the bag turning machine, the rubber is opened and filtered;
[0039] S44: Add the rubber material into an internal mixer, add 12 parts of vulcanizing agent, mix at 105°C for 3 minutes, produce the rubber, and then turn over on a bag turning machine, roll on an open mixer, and produce sheets to obtain the outer sheath material.
[0040] The outer sheath material is extruded outside the insulation layer to form an outer sheath layer to obtain a cold-resistant and torsion-resistant wind energy control cable.
[0041] Embodiment 2
[0042] Preparation of modified silica
[0043] Pretreatment: Concentrated sulfuric acid and concentrated nitric acid were measured in a volume ratio of 3:1 to prepare a mixed acid solution, white carbon black was added to the mixed acid solution at a solid-liquid ratio of 8g / L, and after ultrasonic dispersion, the temperature was raised to 80°C, and the mixture was refluxed for 20h. After the reaction was completed, the mixture was filtered, and the filter cake was washed with deionized water until the filtrate was neutral. After drying, anhydrous ethylenediamine and N, N-dicyclohexylcarboximide with a volume ratio of 1:1 were added to the mixed solution of anhydrous ethylenediamine and N, N-dicyclohexylcarboximide with a volume ratio of 1:1. The mixture was heated to 120°C, and the mixture was refluxed for 72h. After the reaction was completed, the mixture was filtered. The filter cake was washed with deionized water until neutral, dried and ultrasonically dispersed in xylene with a mass of 10 times the mass of white carbon black, maleic anhydride with a mass of 0.5 times the mass of white carbon black was added, the temperature was raised to 85°C, and the reaction was refluxed for 24 hours. After the reaction was completed, 1 / 2 times the volume of a mixed solution of anhydrous ethylenediamine and N,N-dicyclohexylcarboximide was added, diluted with 50°C anhydrous ethanol, filtered, and the filter cake was washed three times with anhydrous ethanol and deionized water respectively, and then dried for use.
[0044] Take the pretreated silica, add it to the liquid butadiene rubber, stir and mix, add diisopropylbenzene peroxide, heat to 180°C, keep the temperature for 2 hours, and obtain modified silica, wherein the mass ratio of silica, liquid butadiene rubber and diisopropylbenzene peroxide is 2:1.5:0.12.
[0045] The prepared modified silica is used as a raw material for cold-resistant and torsion-resistant wind energy control cables, wherein the filler of this embodiment comprises the following raw materials in parts by weight: 20 parts of short carbon fibers, 10 parts of kaolin, and 20 parts of modified silica. The specific preparation method is as follows:
[0046] S1: The copper rod is drawn, heat treated, tinned, annealed, and twisted to obtain a conductor;
[0047] S2: Wrap the conductor with polyester tape to form an isolation layer;
[0048] S3: Extruding an insulating layer outside the isolation layer;
[0049] S4: Refining the raw materials of the outer sheath to obtain the outer sheath material, specifically:
[0050] S41: 120 parts of EPDM rubber and 20 parts of chlorinated polyethylene are added to an internal mixer and mixed until the rubber wraps around the rotor;
[0051] S42: Add 5 parts of zinc oxide, 1 part of antioxidant, 5 parts of plasticizer, 4 parts of antioxidant and 15 parts of flame retardant, mix for 3 minutes, heat to 120°C, add 60 parts of filler, specifically add short carbon fiber and kaolin first, continue mixing for 3 minutes, add modified white carbon black, mix for 5-6 minutes, and remove glue;
[0052] S43: After 3 times of refining on the bag turning machine, the rubber is opened and filtered;
[0053] S44: Add the rubber material into an internal mixer, add 10 parts of vulcanizing agent, mix at 110°C for 2 minutes, produce the rubber, and then turn over on a bag turning machine, roll on an open mixer, and produce sheets to obtain the outer sheath material.
[0054] The outer sheath material is extruded outside the insulation layer to form an outer sheath layer to obtain a cold-resistant and torsion-resistant wind energy control cable.
[0055] Embodiment 3
[0056] Preparation of modified silica
[0057] Pretreatment: Concentrated sulfuric acid and concentrated nitric acid were measured in a volume ratio of 3:1 to prepare a mixed acid solution, white carbon black was added to the mixed acid solution at a solid-liquid ratio of 6g / L, and after ultrasonic dispersion, the temperature was raised to 75°C, and the mixture was refluxed for 22 hours. After the reaction was completed, the mixture was filtered, and the filter cake was washed with deionized water until the filtrate was neutral. After drying, anhydrous ethylenediamine and N, N-dicyclohexylcarboximide with a volume ratio of 1:1 were added to the mixed solution of anhydrous ethylenediamine and N, N-dicyclohexylcarboximide with a volume ratio of 1:1. The mixture was heated to 125°C, and the mixture was refluxed for 60 hours. After the reaction was completed, the mixture was filtered. The filter cake was washed with deionized water until neutral, dried and ultrasonically dispersed in xylene with a mass of 10 times the mass of white carbon black, maleic anhydride with a mass of 0.7 times the mass of white carbon black was added, the temperature was raised to 85°C, and the reaction was refluxed for 24 hours. After the reaction was completed, 1 / 2 times the volume of a mixed solution of anhydrous ethylenediamine and N,N-dicyclohexylcarboximide was added, diluted with 50°C anhydrous ethanol, filtered, and the filter cake was washed three times with anhydrous ethanol and deionized water respectively, and then dried for use.
[0058] Take the pretreated silica, add it to the liquid butadiene rubber, stir and mix, add diisopropylbenzene peroxide, raise the temperature to 200°C, and keep the temperature for 2 hours to obtain modified silica, in which the mass ratio of silica, liquid butadiene rubber and diisopropylbenzene peroxide is 3:1:0.15.
[0059] The prepared modified silica is used as a raw material for cold-resistant and torsion-resistant wind energy control cables, wherein the filler of this embodiment comprises the following raw materials by weight: 15 parts of short carbon fibers, 5 parts of kaolin, and 40 parts of modified silica. The specific preparation method is as follows:
[0060] S1: The copper rod is drawn, heat treated, tinned, annealed, and twisted to obtain a conductor;
[0061] S2: Wrap the conductor with polyester tape to form an isolation layer;
[0062] S3: Extruding an insulating layer outside the isolation layer;
[0063] S4: Refining the raw materials of the outer sheath to obtain the outer sheath material, specifically:
[0064] S41: 110 parts of EPDM rubber and 40 parts of chlorinated polyethylene are added to an internal mixer and mixed until the rubber wraps around the rotor;
[0065] S42: Add 3 parts of zinc oxide, 3 parts of antioxidant, 5 parts of plasticizer, 3 parts of antioxidant and 10 parts of flame retardant, mix for 2 minutes, heat to 110-120°C, add 80 parts of filler, specifically add short carbon fiber and kaolin first, continue mixing for 4 minutes, add modified white carbon black, mix for 5-6 minutes, and remove glue;
[0066] S43: After 3 times of refining on the bag turning machine, the rubber is opened and filtered;
[0067] S44: Add the rubber material into an internal mixer, add 15 parts of vulcanizing agent, and internally mix at 100°C for 3 minutes to produce the rubber material, then refining it on a bag turning machine, rolling it on an open mixing mill, and producing sheets to obtain the outer sheath material.
[0068] Comparative Example
[0069] The difference between this comparative example and Example 1 is that this comparative example uses ordinary white carbon black.
[0070] The outer sheath material is extruded outside the insulation layer to form an outer sheath layer to obtain a cold-resistant and torsion-resistant wind energy control cable.
[0071] The performance test results of the cold-resistant and torsion-resistant wind energy control cables prepared in Examples 1 to 3 of the present invention and the comparative example are shown in Table 1 below:
[0072] Table 1 Performance test
[0073]
[0074] It can be seen from the data in the above table that the use of the modified silica of the present application as a filler can significantly increase the mechanical properties and cold resistance of the cable, does not crack at low temperatures, and can better adapt to extreme environments.
[0075] The above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit the present invention. Although the present invention is described in detail with reference to the preferred embodiments, it should be understood by those skilled in the art that the technical solutions of the present invention may be modified or replaced by equivalents without departing from the purpose and scope of the technical solutions of the present invention, which should be included in the scope of the claims of the present invention. The techniques, shapes, and structural parts not described in detail in the present invention are all known technologies.
Claims
1. A cold-resistant and torsion-resistant wind energy control cable, characterized in that: The control cable comprises, from the inside to the outside, a conductor, an isolation layer, an insulating layer, and an outer sheath layer extruded outside the insulating layer; the outer sheath layer comprises the following raw materials in parts by weight: 100-120 parts of EPDM rubber, 20-40 parts of chlorinated polyethylene, 3-5 parts of zinc oxide, 60-80 parts of filler, 1-3 parts of antioxidant, 5-10 parts of plasticizer, 3-4 parts of antioxidant, 10-15 parts of vulcanizer, and 10-15 parts of flame retardant; the filler comprises the following raw materials in parts by weight: 15-20 parts of short carbon fiber, 5-10 parts of kaolin, and 20-40 parts of modified white carbon black; The preparation method of the modified white carbon black is as follows: taking the pretreated white carbon black, adding it to liquid butadiene rubber, stirring and mixing, adding dicumyl peroxide, heating to 180-200° C., and keeping the temperature for reaction for 2-3 hours to obtain the modified white carbon black; the pretreatment of the white carbon black is as follows: taking the white carbon black and adding it to the mixed acid solution, ultrasonically dispersing it, heating it to 70-80° C., keeping the temperature for reflux for 20-24 hours, filtering it after the reaction is completed, washing the filter cake with deionized water until the filtrate is neutral, drying it, and adding In a mixed solution of anhydrous ethylenediamine and N, N-dicyclohexylcarboximide, the temperature is raised to 120-125°C, and the mixture is kept at reflux for 48-72 hours. After the reaction is completed, the mixture is filtered, and the filter cake is washed with deionized water until it is neutral. After drying, the mixture is ultrasonically dispersed in xylene, and maleic anhydride is added. The temperature is raised to 80-85°C, and the mixture is kept at reflux for 24-48 hours. After the reaction is completed, 50°C anhydrous ethanol is added for dilution, and the mixture is filtered. The filter cake is washed with anhydrous ethanol and deionized water three times in succession, and then the filter cake is dried for later use.
2. A cold-resistant and torsion-resistant wind energy control cable according to claim 1, characterized in that: The outer sheath layer comprises the following raw materials in parts by weight: 100 parts of EPDM rubber, 30 parts of chlorinated polyethylene, 4 parts of zinc oxide, 70 parts of filler, 2 parts of antioxidant, 8 parts of plasticizer, 3 parts of antioxidant, 12 parts of vulcanizer, and 12 parts of flame retardant.
3. A cold-resistant and torsion-resistant wind energy control cable according to claim 2, characterized in that: The filler comprises the following raw materials in parts by weight: 18 parts of short carbon fibers, 8 parts of kaolin, and 35 parts of modified white carbon black.
4. The cold-resistant and torsion-resistant wind energy control cable according to claim 3 is characterized in that: The mixed acid solution is a mixed solution of concentrated sulfuric acid and concentrated nitric acid, and the volume ratio of the concentrated sulfuric acid to the concentrated nitric acid is 3:
1.
5. A method for preparing a cold-resistant and torsion-resistant wind energy control cable according to any one of claims 1 to 4, characterized in that: The preparation method comprises the following steps: S1: The copper rod is drawn, heat treated, tinned, annealed, and twisted to obtain a conductor; S2: Wrap the conductor with polyester tape to form an isolation layer; S3: Extruding an insulating layer outside the isolation layer; S4: Refining the raw materials of the outer sheath to obtain an outer sheath material, and extruding the outer sheath material outside the insulating layer to form an outer sheath layer.
6. The method for preparing a cold-resistant and torsion-resistant wind energy control cable according to claim 5, characterized in that: The preparation method of the outer sheath material is: S41: adding EPDM rubber and chlorinated polyethylene into an internal mixer, and mixing until the rubber wraps around the rotor; S42: Add zinc oxide, antioxidant, plasticizer, antioxidant and flame retardant, mix for 2-3 minutes, heat to 110-120°C, add short carbon fiber and kaolin in the filler, continue to mix for 2-4 minutes, add modified white carbon black, mix for 5-6 minutes, and remove glue; S43: After 3 times of refining on the bag turning machine, the rubber is opened and filtered; S44: Add the rubber material into an internal mixer, add a vulcanizing agent, and internally mix at 100-110°C for 2-3 minutes to produce the rubber, and then turn the rubber material over on a bag turning machine, roll it on an open mixing mill, and produce a sheet to obtain an outer sheath material.
Citation Information
Patent Citations
Ultra-low-temperature-resistant environment-friendly flexible cable and preparation method thereof
CN109360682A